Microcomputer dictionary and guide - Sippl, Charles J.; Kidd, David A. (Champagne [sic], Ill. : Matrix Publishers, 1976)
The Microcomputer Dictionary must be developed to establish the many facets of microcomputer operations, applications, and newest developments. This first edition attempts to fill this need with over 5000 entries of terms, definitions and product, procedure and applications explanations.
Rev. ed. published as: Microcomputer dictionary. 2nd ed. c1981.
ne 25/08/2021
Ref.
Keywords: Microcomputers; Microelectronics